Parallel transmit pulse design for saturation homogeneity (PUSH) for magnetization transfer imaging at 7T. Issue 1 (10th March 2022) - Leitão, David; Tomi‐Tricot, Raphael; Bridgen, Pip; Wilkinson, Tom; Liebig, Patrick; Gumbrecht, Rene; Ritter, Dieter; Giles, Sharon L.; Baburamani, Ana; Sedlacik, Jan; Hajnal, Joseph V.; Malik, Shaihan J.
Abstract : Purpose: This work proposes a novel RF pulse design for parallel transmit (pTx) systems to obtain uniform saturation of semisolid magnetization for magnetization transfer (MT) contrast in the presence of transmit field B 1 + inhomogeneities. The semisolid magnetization is usually modeled as being purely longitudinal, with the applied B 1 + field saturating but not rotating its magnetization; thus, standard pTx pulse design methods do not apply. Theory and Methods: Pulse design for saturation homogeneity (PUSH) optimizes pTx RF pulses by considering uniformity of root‐mean squared B 1 +, B 1 rms, which relates to the rate of semisolid saturation. Here we considered designs consisting of a small number of spatially non‐selective sub‐pulses optimized over either a single 2D plane or 3D. Simulations and in vivo experiments on a 7T Terra system with an 8‐TX Nova head coil in five subjects were carried out to study the homogenization of B 1 rms and of the MT contrast by acquiring MT ratio maps. Results: Simulations and in vivo experiments showed up to six and two times more uniform B 1 rms compared to circular polarized (CP) mode for 2D and 3D optimizations, respectively. This translated into 4 and 1.25 times more uniform MT contrast, consistently for all subjects, where two sub‐pulses were enough for the implementation and coil used. Conclusion: The proposed PUSH method obtains more uniform and higher MT contrast than CP mode within the same specific absorption rate (SAR) budget.